(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Bhagawan WS, Suproborini A, Putri DLP, Nurfatma A, Putra RT. 2022. Ethnomedicinal study, phytochemical characterization, and pharmacological confirmation of selected medicinal plant on the northern slope of Mount Wilis, East Java, Indonesia. Biodiversitas 23: 4303-4313. The traditional usage of plants in ethnomedicine is a valuable resource for human primary healthcare. The effectiveness of herbal medicines and the creation of new drugs are proven by pharmacological and phytochemical verification. This study documented the traditional ethnomedicine knowledge (TEK) on the northern slope of Mount Wilis community in utilizing medicinal plants and revealed the ethnopharmacology relevance of selected medicinal plants. Data on TEK and its practices were collected through in-depth and semi-structured interviews with informants who were selected using purposive sampling and snowball sampling techniques. The phytochemical compounds of the selected medicinal plant were identified using the UPLC-Qtof-MS/MS instrument, while their pharmacological activity was measured in antibacterial tests. The results showed that the community continued to apply TEK that had been passed down by the previous generation through a method called Gethok Tular. The medicinal plant species in the study area were diverse, 82 species from 39 families with various modes of preparation were used to treat seven disease categories. Tithonia diversivolia had the highest use value of 0.65 and it contained 23 phytochemical compounds. In addition, this plant has high pharmacological potential for antibacterial agents.